Test of the electric charge conservation law with Borexino detector. Issue 1 (January 2016) - Vishneva, A; Agostini, M; Appel, S; Bellini, G; Benziger, J; Bick, D; Bonfini, G; Bravo, D; Caccianiga, B; Calaprice, F; Caminata, A; Cavalcante, P; et al.
Abstract: The new limit on the electron lifetime is obtained from data of the Borexino experiment. The expected signal from the e → γν decay mode is a 256 keV photon detected in liquid scintillator. Because of the extremely low radioactive background level in the Borexino detector it was possible to improve the previous measurement by two orders of magnitude.